Cooling during Exercise in Temperate Conditions: Impact on Performance and Thermoregulation - Eijsvogels, T. M. H.; Bongers, C. C. W. G.; Veltmeijer, M. T. W.; Moen, M. H.; Hopman, M. (International Journal of Sports Medicine, 2014)
Exercise-induced increase in core body temperature may lead to the development of hyperthermia (>40.0°C) and/or decreased performance levels. This study examined the effects of wearing a cooling vest during a 5-km time trial on thermoregulatory responses and performance. 10 male masters athletes (42±10 years) performed a 5-km time trial on a motorized treadmill in a climate chamber (25°C, 55% relative humidity) with and without a cooling vest. Split times, heart rate, core-, skin- and cooling vest temperature were measured every 500 m. Subjects also rated thermal comfort and level of perceived exertion. The cooling vest significantly decreased heart rate (p<0.05), decreased skin temperature (p<0.001) and improved thermal comfort (p<0.005) during the time trial. Time to finish the 5-km time trial and pacing strategy did not differ between the control (1 246±96 s) and cooling vest condition (1 254±98 s, p=0.85). Additionally, thermoregulatory responses, maximum core body temperature and level of perceived exertion were not different across conditions (p=0.85, p=0.49, p=0.11, respectively). In conclusion, we demonstrated that wearing a cooling vest during exercise improves thermal comfort but does not enhance performance or decrease core body temperature in male masters athletes under temperate ambient conditions.
Keywords: cooling vest; core body temperature; endurance exercise; athletes; time trial; precooling